The Role of the Creative Economy in Driving Local Economic Growth in the Digital Era - Hasirah; Siti Aisyah; Nurjanna Ladjin; Rudy Irwansyah; M Alit Suryawan (Jurnal Economic Resource, 2025)
The creative economy has become a key foundation for sustainable economic development worldwide, combining culture, creativity, and technology to drive innovation and growth. In Indonesia, this sector has gained significant momentum, contributing substantially to the country's Gross Domestic Product (GDP), creating job opportunities, and enhancing cultural preservation. This study employed a library research method, a data collection approach that involved reviewing various written sources, including scientific journals, books, official reports, and online articles, all of which were relevant to the topic discussed. This method was used to gain a deep understanding of the creative economy's role in driving local economic growth in the digital era. The study found that the creative economy plays a strategic role in driving local economic growth, particularly in the digital era, which opens up various opportunities through the use of technology. Digital transformation enables creative entrepreneurs to reach broader markets, enhance competitiveness, and promote local cultural identity through products rooted in creativity and innovation. This sector's contribution to the national economy is becoming increasingly significant, particularly for MSMEs that can effectively adapt to digital platforms. However, its development still faces challenges, including limited internet access, low digital literacy, and capital constraints. Therefore, a collaborative strategy is needed between the government, the private sector, and the community through digital skills training, infrastructure improvements, and providing access to financing.